Exploring Planning for Teaching Arabic as a Foreign Language at Senior High School: Teacher’s Didactical Competencies - Sanusi, Anwar; Ainin, Moh.; Muassomah, Muassomah; Maulana, Deni; Maimunah, Iffat (Institut Agama Islam Negeri Curup, 2022)
This study aimed to explore teachers’ didactic competencies in planning Arabic language teaching for Non-Native Speaker (NNS) students at the Islamic senior high school level. A qualitative approach with a descriptive method was used in this study. The results of this study showed that the didactic competence of Arabic language teachers in planning Arabic language teaching had not been in line with applicable regulations and guidelines, such as determining core competencies and basic competencies levels, formulating the indicators of competency achievement, setting learning objectives, and developing learning activities by integrating 4C skills in core activities. The foregoing was due to the lack of teachers’ understanding and experiences in developing syllabi and preparing lesson plans. It is hoped that this study can be a reference for Arabic language teachers at all levels of Islamic schools, especially in developing a syllabus and preparing appropriate lesson plans, so that learning processes can be carried out effectively.